2001
DOI: 10.1590/s0004-282x2001000600019
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic meningioma: case report

Abstract: -Intracranial meningiomas continue to challenge our best clinical efforts to eliminate them once discovered and deemed appropriate for treatment. Malignant meningiomas constitute 10% to 15% of all meningiomas and limited information exists regarding adjuvant treatment. The external whole brain irradiation is recommended. Traditional chemotherapy has proven ineffective; thus, new chemotherapeutic agents and new methods of delivery should be developed. Immunotherapy may be considered for patients with malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
4
0
3
Order By: Relevance
“…Ki67 antigen recognized by MIB1 antibody) [10]. In this respect, arachnoid "cap" cells, from which meningiomas arise, have a slow rate of cell division [2], and therefore a high mitotic activity cannot be expected in their tumoral transformations. Noticeably, MIB1 immunostaining was ineffective in our series (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Ki67 antigen recognized by MIB1 antibody) [10]. In this respect, arachnoid "cap" cells, from which meningiomas arise, have a slow rate of cell division [2], and therefore a high mitotic activity cannot be expected in their tumoral transformations. Noticeably, MIB1 immunostaining was ineffective in our series (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…16 In another study also it was mentioned that headache is one of the symptom which is associated with meningioma. [17][18][19] In this study it was observed that the meningioma was associated with vomiting. In one of the study it was indicated that one of the symptoms of meningioma is vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 8% of meningiomas are considered "atypical" (WHO grade 2) and tend to have a higher incidence of recurrence (2). Th e presence of necrosis, excessive mitotic activity, and evidence of brain invasion are histologic features that result in an "atypical" classifi cation (3). Anaplastic meningiomas (WHO grade 3) account for <1% all meningiomas and have a much shorter mean survival time, with a 5-year-survival rate of approximately 64%, compared with 95% for atypical meningiomas (2).…”
Section: Discussionmentioning
confidence: 99%